Optimum Reactive Power Dispatch for Alleviation of Voltage Deviations - Abraham Lomi; Dhadbanjan Thukaram (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
This paper presents a non-linear optimization algorithm for alleviation of under-voltage and over-voltage conditions in the day-to-day operation of power networks. Voltage control for varying load and generation conditions can be achieved by coordinated control of switchable shunt VAR compensating (SVC) devices, on load transformer taps (OLTC) and generators excitation. The proposed algorithm for voltage control uses a non-linear least square minimization technique. Results obtained for 6-Bus Ward-Hale system and a modified IEEE 30-Bus system are presented for illustration purposes.